Arctic soil water chemistry in dry and wet tundra subject to snow addition, summer warming and herbivory simulation - Rasmussen, Laura H.; Michelsen, Anders; Ladegaard-Pedersen, Pernille; Nielsen, Cecilie S.; Elberling, Bo (Soil biology & biochemistry, 2020)
Multiple and rapid environmental changes in the Arctic have major consequences for the entire ecosystem. Soil water chemistry is one component with important implications for understanding climate feedbacks, plant growth, microbial turnover and net greenhouse gas emissions. Here we assess the contrasting growing season soil water chemistry in a Low arctic Greenlandic mesic tundra heath and a fen, which have been subjected to factorial treatments of summer warming using open top chambers (OTCs), snow addition using snow fences, which increase soil temperature in late winter, and shrub removal mimicking herbivory attack. Dissolved Organic Carbon (DOC) and plant nutrients, including NO3−, NH4+, PO42+ and total dissolved N were measured during multiple growing seasons (2013–2016) to quantify the treatment effects on nutrient availability in two dominating, but contrasting, vegetation types. Ambient nutrient concentrations in the mesic tundra heath decreased throughout the growing season and increased during senescence, while concentrations were highest during peak growing season in the fen. The content of NH4+ and DOC were highest in the fen, whereas NO3− was highest in the mesic tundra heath. The fen had no seasonal pattern. Summer warming in the mesic tundra heath did not change the availability of nutrients, but in combination with shrub removal, both NO3− and DOC concentrations increased, likely due to reduced plant uptake. Shrub removal alone increased NO3− in one growing season, and, combined with snow addition, increased DOC. Significant effects of shrub removal were mostly found in 2016. Snow addition combined with summer warming increased DOC and total N concentrations and highlights the potential loss of dissolved C from the ecosystem. In the fen, shrub removal alone and combined with summer warming decreased DOC. Snow addition alone and in combination with summer warming similarly decreased DOC. In the mesic tundra heath, shrub removal caused higher soil water contents in all years. In the dry and warm 2016, it meant <10% soil water content in controls and 15–20% in shrub removal plots during the peak growing season, which may have relieved soil moisture limitation on mineralization rates in the latter. We conclude that soil water chemistry is vegetation-specific, and that treatment effects are surprisingly limited when comparing multiple years with contrasting precipitation patterns. Herbivory may have larger impact in very dry, warm summers and, together with extreme weather events, exert similar or larger effects than four years of temperature manipulations. The effects of summer warming or increased winter snow depend on ecosystem type and moisture status of the soil. The combination of multi-year and multi-site studies therefore seem important for understanding future biogeochemical dynamics in Arctic landscapes. •Soil N and DOC had mixed responses to climate change in a fen and a mesic tundra.•Deeper winter snow decreased DOC content in the fen, but increased DOC in the heath.•Simulated herbivory resulted in increased plant-available N and DOC.•Herbivory had most effect during drought, likely due to less plant transpiration.